Hepatoprotective studies on methanolic extract of whole plant of Lindernia ciliata - Pallerla Praneetha; Vanapatla Swaroopa Rani; Yellu Narasimha Reddy; Bobbala Ravi Kumar (Bangladesh Pharmacological Society, 2014)
Lindernia ciliata is traditionally used in the treatment of jaundice. In the present study, the methanolic extract of L. ciliata was evaluated for its hepatoprotective activity in paracetamol, ethanol and D-galactosamine intoxicated rats. The activity of the extract was assessed on the basis of improvement in the altered level of various serum biochemical parameters and in the changes occurred in the histology of liver of the rats. The extract was also investigated for its antioxidant potential by employing different in vitro methods. Among the three test doses of extract, 200 mg/kg was found to be the most effective dose. The significant (p<0.01) hepatoprotective and antioxidant activities exhibited by the extract, in different in vivo models and in vitro studies respectively may be attributed to the flavonoids and phenolic compounds present in the extract.